2018
DOI: 10.3390/jcm7080222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resilience in Internet Addiction among Adolescents between Sexes: A Moderated Mediation Model

Abstract: The behavioral inhibition/activation systems (BIS/BAS) have been considered to be predictors of Internet addiction, mediated by clinical variables such as anxiety and depression. However, resilience has been suggested as a protective factor toward Internet addiction, and certain sex differences in resilience buffering the effects of vulnerability have been reported. Thus, the aim of this study was to identify any role of resilience that might moderate the effects of BIS/BAS on Internet addiction through multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 74 publications
(90 reference statements)
10
50
0
Order By: Relevance
“…To aid in understanding the association of internet addiction and NSSI, multinominal logistic regression analyses were used to estimate the adjusted odds ratios (aORs) and 95% CIs of internet addiction and possible internet addiction for participants engaged in less-frequent or more-frequent NSSI separately, and different covariates were adjusted in 3 models to examine the robustness of the associations. In model 1, we adjusted for demographic characteristics of participants, including provinces (Anhui, Guangdong, Heilongjiang, Hubei, and Yunnan), sex (male or female), age groups (11)(12)(13)(14)(15)(16)(17), and 18-20 years), grade (junior high school or senior high school), and ethnicity (Han or others). In model 2, we also adjusted for covariates of socioeconomic status and family environment, including family income (<$150, $150-850, or >$850/mo), which was divided according to local economic level and referred to in a previous study, 30 family structure (single parent/restructured family, grandparents' family, combined family, or core family/stem family), single-child family (yes or no), parents' educational level (college or above, senior high school/technical school, or junior high school or below), parenting styles (strict, pampered, neglect or frequently changing, or open-minded).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To aid in understanding the association of internet addiction and NSSI, multinominal logistic regression analyses were used to estimate the adjusted odds ratios (aORs) and 95% CIs of internet addiction and possible internet addiction for participants engaged in less-frequent or more-frequent NSSI separately, and different covariates were adjusted in 3 models to examine the robustness of the associations. In model 1, we adjusted for demographic characteristics of participants, including provinces (Anhui, Guangdong, Heilongjiang, Hubei, and Yunnan), sex (male or female), age groups (11)(12)(13)(14)(15)(16)(17), and 18-20 years), grade (junior high school or senior high school), and ethnicity (Han or others). In model 2, we also adjusted for covariates of socioeconomic status and family environment, including family income (<$150, $150-850, or >$850/mo), which was divided according to local economic level and referred to in a previous study, 30 family structure (single parent/restructured family, grandparents' family, combined family, or core family/stem family), single-child family (yes or no), parents' educational level (college or above, senior high school/technical school, or junior high school or below), parenting styles (strict, pampered, neglect or frequently changing, or open-minded).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness was measured by using the revised version of the Loneliness Scale, which was developed by Li et al 27 Previous studies have suggested that both NSSI and internet addiction were associated with a wide range of demographic characteristics and socioeconomic status, 15,16 which should be adjusted when examining the association of internet addiction with NSSI. We used a self-designed questionnaire to collect socioeconomic, familial, and parenting variables, including age, sex, ethnicity, family income, family structure, single-child family, parents' educational level, and parenting style.…”
Section: Instrumentsmentioning
confidence: 99%
“…Similarly, the discrepancy between the actual self and the ideal self had a significant influence on the tendency to engage in pathological gaming, indicating that addicted gamers try to escape from the real world or the self via internet gaming [ 69 , 70 ]. Furthermore, IGD patients tend to have low levels of resilience (i.e., the ability to overcome, recover from, or adapt to significant adversity) [ 71 , 72 ], which is noteworthy because resilience plays a protective role in IGD [ 73 ]. Indeed, several studies have found that self-efficacy is correlated with levels of resilience, which is not surprising given that self-efficacy is considered an element of resilience [ 74 ] and that general self-efficacy is closely associated with resilience [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, psychosocial resilience, such as positive emotions, optimism, humor, cognitive flexibility, and reappraisal could attenuate stress-induced psychopathology [21]. Thus, resilience was reported to be a buffering factor against Internet addiction [22]. Furthermore, resilience was reportedly lower among adolescents with IGD according to questionnaire assessments [15].…”
Section: Introductionmentioning
confidence: 99%